Effectiveness of the Ecology and Biodiversity Module Integrated with the Pancasila Student Profile on Learning Outcomes of Seventh-Grade Students - Tarigan, Grace Amelia Br; Hardinata*, Aristo; Sihombing, Rizky Agassy (Jurnal IPA & Pembelajaran IPA, 2025)
One of the main challenges in science education is the low conceptual understanding of students in ecological and biodiversity topics. This study aims to determine the effectiveness of the ecology and biodiversity module integrated with the pancasila student profile in improving the learning outcomes of seventh-grade students at SMP Negeri 6 Medan. The research employed a quasi-experimental design with a pretest-posttest control group to measure students' understanding before and after using the module. The sample consisted of 30 students from class VII-F, selected through purposive sampling. Data were collected using pretest and posttest assessments, and the effectiveness of the module was analyzed using the N-gain score formula to determine the improvement in students' learning outcomes. The results showed a significant increase in students' understanding, with an average pretest score of 28.10, which improved to 78.73 in the posttest. The calculated N-gain score was 0.70 (seventy percent), placing the module in the moderate to high effectiveness category. Additionally, 53.3 percent of students achieved a high learning gain, while 46.7 percent showed a moderate gain, indicating that the module effectively facilitated conceptual understanding. Based on these findings, the ecology and biodiversity module integrated with the pancasila student profile is proven to be effective in enhancing students learning outcomes. This module is recommended for broader implementation in junior high school science learning to support student-centered and character-based education in alignment with the pancasila student profile framework